Deficient irrigation of vegetable crops - A. Yu. Fedosov; A. M. Menshikh; M. A. Ivanova (Овощи России)
Water is one of the main factors for the production of vegetable crops due to its crucial role in the absorption and transport of nutrients, temperature regulation and some physiological processes, including photosynthesis. Considering the growing needs of a growing population for food and nutrients, a significant part of agricultural research is focused on improving the use efficiency (WUE - Water use efficiency) and saving water without reducing yields. Given the difficulty of increasing WUE through selection due to the tradeoff between photosynthesis and transpiration, agronomic strategies are needed. Due to the shallow root system and the fresh sale of vegetable products, vegetable crops are relatively more sensitive to moisture than field crops. Deficit irrigation (DI) is a direct approach to saving water by reducing irrigation to increase water productivity (WP - Water productivity). Regulated deficit irrigation (RDI) and partial root drying (PRD) are two widely used DI planning methods along with the classic DI approach. We searched the peer-reviewed literature for studies reporting yield differences in vegetable crops subjected to irrigation deficits. The search was conducted on Google Scholar and Web of Science using various combinations of the following keywords: vegetable crop yield and irrigation deficit or moisture shortage or water shortage or drought. Moderate levels of water stress (<65% FI) adversely affect vegetable yields regardless of external factors such as soil structure, climate and production system. This level of irrigation is justified for regions where water restrictions are already in place or forecast. Based on WP growth, irrigation levels as low as 35–50% FI for tomato and pepper, and 50–65% FI for onions and <35% FI for eggplant and watermelon are optimal for areas with severe water scarcity. However, a higher water deficit may also have an adverse effect on quality in terms of reduced fruit/root/bulb size.